SOBRECARGA DEL CIRCUITO ELÉCTRICO DE LAS CALLES CALDERÓN ENTRE JUAN X MARCOS Y VARGAS MACHUCA - RIVERA GALARZA, MARCO ANTONIO (2018)
In the city of Babahoyo in the month of September during the days 23 and 24 of that month, the celebrations of the Virgin of the Mercedes are celebrated, and it is typical of those parties that the carousels, mechanical games and the so-called barracks are installed, the latter are stalls or wooden shops, in which the people who own these posts live, so they need the basic service of electric power. These posts are usually delimited between Juan X Marcos streets up to the second street and go from Sucre street to Calderón street. Each time these positions come to the city they make use of the electrical network, for the lighting of said stores, obtaining energy to be able to develop their economic and daily activities during the period of time they are in the sector. In the period of stay of the barracks these create greater demand exceeding the installed capacity of the circuit However, every time that the barracks are installed in this sector, there are energy cuts, which are practically traditional in these festivals, in the town where the people who live there settle and know that each time the barracks, there will be a power cut. After observing this problematic situation that arises in this sector, establishing a cause-effect relationship between power cuts due to the arrival of the barracks to the sector.